(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Inaccurate placement of VP shunt catheter is related to shunt failure. Objective: The objective of this study was to determine the accuracy of ventricular catheter placement during ventriculoperitoneal shunt operations using the freehand technique. Methodology: This prospective observational study included all patients from a single institution who underwent a ventriculoperitoneal shunt procedure in which a new ventricular catheter was placed between September 2013 and August 2016 for a period of three (03) years. Data abstracted for each patient included age, sex, diagnosis, site and side of ventricular catheter placement. Postoperative CT scan images were reviewed for accuracy of ventricular catheter placement. Results: There were 140 patients included in the study; accuracy ventricular catheter tip placement were 55 (39.28%) using freehand technique. Conclusion: Mechanical malfunction and infection are the most significant problems associated with shunts for the treatment of hydrocephalus. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 59-63